2019
DOI: 10.1038/s41598-019-49813-7
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetic patterns associated with an ascidian invasion: a comparison of closely related clades in their native and introduced ranges

Abstract: Environmentally induced epigenetic modifications have been proposed as one mechanism underlying rapid adaptive evolution of invasive species. Didemnum vexillum is an invasive colonial ascidian that has established in many coastal waters worldwide. phylogenetic analyses have revealed that D. vexillum populations consist of two distinct clades; clade B appears to be restricted to the native range (Japan), whereas clade A is found in many regions throughout the world, including New Zealand. The spread of D. vexil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 94 publications
1
8
0
Order By: Relevance
“…Didemnum vexillum must be able to adapt to a wide range of environments in its worldwide introduction range. Chimerism (Casso et al, 2019a) and epigenetic changes (Hawes et al, 2019) have been suggested as potential mechanisms enhancing its adaptive capacity, and the microbiome is likely to play a significant role as well. We found that the microbiome composition of the introduced clade of D. vexillum is significantly influenced by temperature, genetics of the host, and geographic distance.…”
Section: Discussionmentioning
confidence: 99%
“…Didemnum vexillum must be able to adapt to a wide range of environments in its worldwide introduction range. Chimerism (Casso et al, 2019a) and epigenetic changes (Hawes et al, 2019) have been suggested as potential mechanisms enhancing its adaptive capacity, and the microbiome is likely to play a significant role as well. We found that the microbiome composition of the introduced clade of D. vexillum is significantly influenced by temperature, genetics of the host, and geographic distance.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental epigenetics has been examined in few marine invertebrate species (Marsh and Pasqualone, 2014;Ardura et al, 2017;Gavery and Roberts, 2017;Gonzalez-Romero et al, 2017;Li et al, 2017;Dixon et al, 2018;Liew et al, 2018;Baums et al, 2019;Hawes et al, 2019). While epigenetics can encompass a variety of non-genetic mechanisms such as histone modifications and small non-coding RNAs, the majority of marine environmental epigenetics research has focused on DNA methylation, in which cytosines, typically in a CpG dinucleotide context, contain a methyl group (Eirin-Lopez and Putnam, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, within the phylogenetic tree, Phlebobranchia and Aplousobranchia show a closer relationship with Thaliaceae, which is also a Tunicata class different from Ascidiacea, whereas Stolidobranchia remains a distinct and monophyletic group (Delsuc et al, 2018). Over the course of several decades, the Ascidiacea have been shown to be an important class for ecological species because of their invasive potential (Zhan, Briski, Bock, Ghabooli, & MacIsaac, 2015) along with their ability to adapt to new environments (Hawes et al, 2019). Transportation of ascidians attached to ship hulls as fouling material and within the ballast water of ships has enabled them to invade new territories (Lambert, 2007).…”
Section: Introductionmentioning
confidence: 99%